P416 Longitudinal relationship and sexual health outcomes for adolescent and young adults with pelvic inflammatory disease. (14th July 2019) - Trent, Maria; Perin, Jamie; Toppins, Jacquelin; Rowell, Julia; Huettner, Steven; Anders, Jennifer; Rothman, Richard; Matson, Pamela; Gaydos, Charlotte
Abstract : Background: Many adolescent and young women (AYA) remain in relationships with their sexual partners at 3-months post-PID, but little is known about how those relationships continue to evolve and integrate risk reduction behaviors. The purpose of this study is to examine 12-month longitudinal sexual and reproductive health behaviors post-PID. Methods: Participants in the Technology Enhanced Community Health Nursing Study (N=286), a large randomized controlled trial of an intervention to improve PID outcomes were enrolled in quarterly post-trial telephone follow-up interviews. This analysis presents data from participants who completed 12 months of follow-up (N=72). Participants were queried about interim symptoms, sexual and reproductive behaviors, and clinical outcomes such as recurrent STI, pregnancy, chronic abdominal pain) and relationship status. Data were analyzed using descriptive and logistic regression analyses. Results: Of 72 participants who completed the 12-month post-trial follow-up, 33 were in the intervention group, and 39 were in the control group, and 42 (58%) reported new partners in the last 12 months. Participants with new partners were not more likely to report having an STI than women without new partners (estimated odds ratio 1.6, 95%CI 0.5, 4.6, p = 0.470) or to have used contraceptives in the past 12 months (OR = 4.5 95% CI 0.3, 244.5, p = 0.301), but are more likely to have had lower abdominal pain (OR 5.6 95% CI 1.8, 18.9, p=0.001). Most women (86%) reported condom use in the prior 12 months, but there were no differences in condom use over the last year based on new partner status. Conclusion: Most AYA who experience PID acquire new partners during the year post-PID, but are not more likely to use condoms at 12 months. Given the increased association with lower abdominal pain, booster STI risk reduction strategies may be indicated to prevent associated sequelae among affected patients. Disclosure: No significant relationships.